Perlindungan Hukum Terhadap Penyewa Tanah Dari Pengelola Tanah Yang Hendak Dijual Pemilik Tanah Sebelum Masa Sewa - Tegar Ananta Prakarsa; Glady Arga Maroena; Tiyas Vika Widyastuti; Evy Indriasari; Nuridin (Catalist Indo Publisher, 2025)
A lease agreement is an agreement set forth in a written agreement with the contents of the parties binding themselves to each other within a specified time and has an agreed price value that gives rise to an obligation for the tenant to pay for the goods or buildings he rents, but in practice the researcher found that there are things that harm the tenant such as by selling land without the knowledge of the party The tenant of the land certainly cannot be ignored, considering that the principle of an engagement agreement is good faith in an agreement, good faith means that one party intends not to interfere with allies or public interest The type of method used by the author is using the library research method (Library Research), which is a method used by studying literature books, legislation, and other written materials. The results of this study show the Legal Protection of Land Tenants from Land Managers Who Want to Sell Land Owners Before the Lease Period and Land Rental Agreements from Land Managers Who Want to Be Sold by Land Owners. Based on the results of this research, it is hoped that it will be material for information and input from students, academics, and all parties in need, especially within the Faculty of Law, Pancasakti University of Tegal